2011
DOI: 10.1111/j.1538-7836.2011.04277.x
|View full text |Cite
|
Sign up to set email alerts
|

Atherothrombosis and the role of antiplatelet therapy

Abstract: To cite this article: Steg PhG, Dorman SH, Amarenco P. Atherothrombosis and the role of antiplatelet therapy. J Thromb Haemost 2011; 9 (Suppl. 1): 325-332.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 72 publications
(64 reference statements)
0
25
0
1
Order By: Relevance
“…A newer agent, prasugrel, has a faster onset and more inhibition of platelets than clopidogrel. 26 These pharmacodynamics are favorable for potential use in endovascular therapy with partial recanalization or as an adjunctive agent to mechanical or fibrinolytic local AIS therapy. Stent implantation necessitates periprocedure antiplatelet therapy to reduce the risk of acute and delayed stent thrombosis.…”
Section: Figure 1 Platelet Aggregation and Antiplatelet Medication Inmentioning
confidence: 99%
See 2 more Smart Citations
“…A newer agent, prasugrel, has a faster onset and more inhibition of platelets than clopidogrel. 26 These pharmacodynamics are favorable for potential use in endovascular therapy with partial recanalization or as an adjunctive agent to mechanical or fibrinolytic local AIS therapy. Stent implantation necessitates periprocedure antiplatelet therapy to reduce the risk of acute and delayed stent thrombosis.…”
Section: Figure 1 Platelet Aggregation and Antiplatelet Medication Inmentioning
confidence: 99%
“…The mechanism of action of aspirin is well known to be related to thromboxane A2 and Cox I. 26 Aspirin offers a small but significant reduc- Selected intra-arterial thrombolysis studies reporting the use of adjunctive antithrombotic agents Lee et al 14 Deshmukh et al 16 Mangiafico et al 17 Qureshi et al 15 No. of patients 26 Abbreviations: IA ϭ intra-arterial; ICH ϭ intracranial hemorrhage.…”
Section: Figure 1 Platelet Aggregation and Antiplatelet Medication Inmentioning
confidence: 99%
See 1 more Smart Citation
“…These risk factors are similar across the various arterial beds affected. Hence, many patients have silent or clinically overt disease at two or more sites 14 . The International Reduction of Atherothrombosis for Continued Health (REACH) registry has shown that 25% of patients with coronary artery disease, 40% with cerebrovascular disease, and 62% with peripheral artery disease 15 have clinically overt systemic disease 16 .…”
Section: Platelets and Atherothrombosismentioning
confidence: 99%
“…[1][2][3] The use of antiplatelet agents has proven beneficial and is supported by the American College of Cardiology Foundation/American Heart Association guidelines for secondary prevention of atherothrombosis and the guidelines for patients with unstable angina/non-ST-segment elevation myocardial infarction (MI). 2,4 The use of thienopyridines (clopidogrel and prasugrel) and nonthienopyridines (ticagrelor) to antagonize P2Y 12 receptors on the surface of platelets helps reduce the risk of ischemic events and is recommended in the setting of acute coronary syndrome (ACS) and percutaneous coronary interventions (PCIs).…”
mentioning
confidence: 99%